Konsep Hijab Muslimah Perspektif Kader Muslimah Wahdah Islamiyah Makassar: The Concept of Muslimah Hijab from the Perspective of Islamic Law (A Study on the Muslimah Cadets of Wahdah Islamiyah Makassar) - Rosmita, Rosmita; Sartini Lambajo; Fitria, Fitria (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
The research aims to understand the concept of hijab among the female cadres of Wahdah Islamiyah Makassar and from the perspective of Islamic Law. This research uses field research, which is a systematic study that collects data in the field and is correlational with a quantitative approach. The research findings presented in this thesis are as follows: First, the concept of hijab among the female cadres of Wahdah Islamiyah Makassar in terms of knowledge and understanding falls into the category of knowing and understanding the concept of hijab. As for the level of agreement from the perception and attitude of the cadres, it shows that 67.38% or equivalent to 527 people disagree with the currently trending hijab concept, while conversely, 32.62% of the cadres agree with the currently trending hijab concept. Secondly, the concept of Muslim women's hijab in the perspective of Islamic Law is a hijab that must adhere to the conditions that must be met in the use of Shari'ah-compliant hijab. This writing is expected to contribute to society, especially for Muslim women, and to assist the Wahdah Islamiyah Institute in Makassar in understanding the extent of its cadres' knowledge, understanding, perception, and attitude towards the concept of Shari'ah-compliant hijab.